A Novel Cryptographic Technique for Cloud Environment Based on Feedback DNA - Sharfuddin, Nadia; Anwer, Faisal; Ali, Salman (International Journal of Experimental Research and Review, 2023)
Abstract: In the era of cloud computing, ensuring data security is crucial for users and organizations. This paper presents an innovative approach called F-DNAES, which combines DNA cryptography and the Advanced Encryption Standard (AES) algorithm, to enhance data security in cloud-based environments. The proposed methodology focuses on securing data during its transmission and storage in the cloud. By leveraging the unique properties of DNA, such as its storage capacity and stability, along with the robustness of AES encryption, F-DNAES provides a highly secure and efficient solution. The proposed method also ensures the authentication of the Data owners and the users. The F-DNAES model effectively mitigates potential security threats such as phishing attacks, collision attacks, and password guessing attacks. It also offers superior performance in terms of key generation, encryption, and decryption processes. The proposed approach can be applied to various cloud-based scenarios, including IoT infrastructure, web-based applications, and network security. F-DNAES contributes to strengthening data privacy and security, providing users with a trusted and reliable solution in cloud environments.